2004
DOI: 10.1182/blood-2003-01-0237
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HbC and HbS, but not HbA, results in activation of K-Cl cotransport activity in transgenic mouse red cells

Abstract: Elevation of K-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Positively charged Hb S and Hb C are associated with dehydration via up-regulation of the KCl cotransporter. [43][44][45] Notably, diffuse Hb strains would be predicted to have increased positive charge relative to single strains because ␤ dminor has a net loss of 2 negative residues, resulting in a pI of 7.85 versus 7.13 in ␤ S/T and ␤ dmajor . Whether this translates into a corresponding increase in KCl cotransport activity awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Positively charged Hb S and Hb C are associated with dehydration via up-regulation of the KCl cotransporter. [43][44][45] Notably, diffuse Hb strains would be predicted to have increased positive charge relative to single strains because ␤ dminor has a net loss of 2 negative residues, resulting in a pI of 7.85 versus 7.13 in ␤ S/T and ␤ dmajor . Whether this translates into a corresponding increase in KCl cotransport activity awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Expression of Hb S or C in transgenic mice also increases red cell KCC activity. 7 Recently, we demonstrated an abnormal response to acid pH in SS RBCs that was partially corrected by incubation with the sulfhydryl reducing agent, dithiothreitol. 8 These findings suggested that regulation of KCC is abnormal in SS RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,12 However, these studies, like flux studies, are complicated by varying numbers of reticulocytes (or young cells) in unfractionated SS blood, which preclude comparisons of KCC-mediated volume reduction in SS and AA cells. We recently compared the RVD mediated by KCC and stimulated by cell swelling and acid pH in SS and AA reticulocytes by tracking the changes in reticulocyte CHC by means of density gradient analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The C57 (background) mouse and full KO mice models expressing HbE and HbS or HbA are used as controls. In selective cases, the HbA full KO mouse model is compared but found to be limited due to its RBC thalassemic characteristics [37] [38]. …”
Section: Introductionmentioning
confidence: 99%